2018
DOI: 10.15408/aiq.v10i1.4563
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Banking and Green Banking for Sustainable Development: Evidence from Bangladesh

Abstract: Green banking is an integral part of Islamic banking that makes a basis of environmental protection. This study attempts to examine the relationship between Islamic banking and green banking that contribute to sustainable development. The study has used the primary data through a structural questionnaire that includes various dimensions on green banking of Islamic banking in Bangladesh. The investigation revealed that Islamic banks had made a significant contribution to green banking that improves the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 3 publications
(5 reference statements)
0
15
0
1
Order By: Relevance
“…As far as a critical literature review is concerned, there is a comprehensive agreement among researchers about the lack of available literature on GB. The literature does not fully explain the barriers to the adoption of GB products and services and requires further investigation (Sahoo et al, 2016;Iqbal et al, 2018;Uddin & Ahmmed, 2018;Bukhari et al, 2019;Julia & Kassim, 2019;Bouteraa et al, 2020aBouteraa et al, , 2020b. Furthermore, all the previous papers on GB adoption rates were based on descriptive statistics.…”
Section: Journal Of Sustainabilitymentioning
confidence: 99%
“…As far as a critical literature review is concerned, there is a comprehensive agreement among researchers about the lack of available literature on GB. The literature does not fully explain the barriers to the adoption of GB products and services and requires further investigation (Sahoo et al, 2016;Iqbal et al, 2018;Uddin & Ahmmed, 2018;Bukhari et al, 2019;Julia & Kassim, 2019;Bouteraa et al, 2020aBouteraa et al, , 2020b. Furthermore, all the previous papers on GB adoption rates were based on descriptive statistics.…”
Section: Journal Of Sustainabilitymentioning
confidence: 99%
“…The research is conducted in order to find out the bankers' perceptions over practices of green banking in commercials bank of Kathmandu Valley. Sustainable development in mitigating the institutional barriers and challenges of market for investment allocation is possible by the green banking practices (Uddin and Ahmmed, 2018). From the study, it is found that majority of the bankers have knowledge on such practices and the top most popular green banking practices in banks are mobile banking, online banking, saving paper, green saving account and ethical banking.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Tu & Yen (2015) have further argued that green banking practices in developing countries, as in Vietnam, is complemented by e-banking adoption for acquiring the maximum environmental benefits. Rishal and Joshi's (2018) argument about green banking tools, techniques, and equipment helping in minimizing internal carbon footprints and external carbon emissions to safeguard the environment and Uddin and Ahmmed's (2018) assertion about investment in green projects for the sustainable development of financial institutions are noteworthy in this regard. In this sense, Sahoo and Nayak (2008) suggested the promotion of green banking practices in consideration of environmental and ecological aspects and talked about the "Green Channel Counter" to go ahead for innovation of 'green bank'.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of green banking has been a subject of significant concern for researchers and scholars in recent years. Such interest has carried about a lot of arguments on the subject, which has led to numerous studies on it in the area of green banking over the years (Uddin and Ahmmed, 2018).…”
Section: Review Of the Literaturementioning
confidence: 99%